First evidence of Cas9 expression during CRISPR-Cas containing megaphage infection - Niemi, Meeri (2024)
Bacteriophages, or phages, are viruses that infect bacteria. Recently, many megaphages with large (over 500 kilo base pairs) genomes have been discovered. Metagenomic analyses show that several phages, including some megaphages, encode a CRISPR-Cas system, an adaptive immune system commonly associated with prokaryotes. These systems consist of CRISPR repeat-spacer arrays and Cas proteins that enable the system to target foreign genetic material in a sequence-specific manner. Some phage-encoded CRISPR-Cas systems have been shown to target host bacterium genome, while others are thought to target competing phages, but empirical evidence is scarce. This research seeks to elucidate the functionality of CRISPR-Cas systems in megaphages, which often exhibit incomplete systems with unclear purpose. In this study, five megaphages (genome size over 600 kilo base pairs) isolated from Lake Jyväsjärvi were studied. Phage host range was determined with titration experiments, and the phages were found to primarily infect species of Flavobacterium. The life cycle of phage Elf16 was determined by measuring host optical density, calculating plaque forming units during infection, and by performing an adsorption to host test. The Elf16 life cycle was found to be lytic, with lysis occurring gradually and starting at roughly three hours post-infection. Thin section samples of the phage infection were imaged using transmission electron microscopy, and the phage particles were shown to be large and have a contractile tail. Images also depict the Elf16 life cycle, which matches the life cycle demonstrated by measuring the optical density and plaque forming units. Elf16 genome was analysed, but no match was found between the CRISPR spacers of the phage and the genome of its isolation host. It is possible that the purpose of the phage CRIPSR-system is to attack host genome, but it is not a requisite for a successful infection. To assess the functionality of the Elf16 CRISPR-Cas system, Cas9 gene expression was measured using qPCR. The findings suggested significant Cas9 expression during early stages of infection, therefore hinting at a potentially functional system.